Mapping and molecular cloning of the phn (psiD) locus for phosphonate utilization in Escherichia coli. - Wanner, B L (1990)
The Escherichia coli phn (psiD) locus encodes genes for phosphonate (Pn) utilization, for phn (psiD) mutations abolish the ability to use as a sole P source a Pn with a substituted C-2 or unsubstituted hydrocarbon group such as 2-aminoethylphosphonate (AEPn) or methylphosphonate (MPn), respectively. Even though the E. coli K-12 phosphate starvation-inducible (psi) phn (psiD) gene(s) shows normal phosphate (Pi) control, Pn utilization is cryptic in E. coli K-12, as well as in several members of the E. coli reference (ECOR) collection which are closely related to K-12. For these bacteria, an activating mutation near the phn (psiD) gene is necessary for growth on a Pn as the sole P source. Most E. coli strains, including E. coli B, are naturally Phn+; a few E. coli strains are Phn- and are deleted for phn DNA sequences. The Phn+ phn(EcoB) DNA was molecularly cloned by using the mini-Mu in vivo cloning procedure and complementation of an E. coli K-12 delta phn mutant. The phn(EcoB) DNA hybridized to overlapping lambda clones in the E. coli K-12 gene library (Y. Kohara, K. Akiyama, and K. Isono, Cell 50:495-508, 1987) which contain the 93-min region, thus showing that the phn (psiD) locus was itself cloned and verifying our genetic data on its map location. The cryptic phn(EcoK) DNA has an additional 100 base pairs that is absent in the naturally Phn+ phn(EcoB) sequence. However, no gross structural change was detected in independent Phn+ phn(EcoK) mutants that have activating mutations near the phn locus.